A case report of Progressive subluxation leading to an anterior dislocation of the hip following sliding hip screw fixation for pertrochanteric Extracapsular 4 part fracture neck of femur. Issue 7 (15th May 2015) - Shah, Jaydeep; Marson, Ben A.
Key Clinical Message Unstable 4 part pertrochanteric fractures without lateral cortical support presents considerable technical problem in treatment with high risk of failure with any implant. Anatomical or slight valgus reduction and subchondral central position of the lag screw (TAD <25 mm) reduces the chance of screw cut out and other complications.